베트남 농촌개발 시범사업 컨설팅 - 1차년도 보고서 - 허장 (한국농촌경제연구원, 2008)
This report introduces the results of the consultation for two rural villages in Vietnam to implement the rural development project supported by the Ministry for Food, Agriculture, Forestry, and Fisheries. The Korea Rural Economic Institute (KREI) had performed the project to establish five-year action plans for the villages from November 2006 to April 2007, and this report is based upon the accomplishments made in the first-year (2007~2008). For the period, the KREI and the National Institute for Agricultural Planning and Projection (NIAPP) of Vietnam signed Memorandum of Understanding and implemented projects that had been scheduled in the action plan. Also, two institutes arranged Saemaul Undong Project Management Board organizations as promoting agencies in districts, communes, and villages. NIAPP administered evaluation survey and reported the results as well as final progress report. During the first year project implementation, one of the project villages has been changed to a neighboring village which caused a delay of the project; however, the project has proceeded without big difficulties and as planned. It is hoped that the construction of Vietnamese model of rural development will also proceed with positive consequences. Correspondence: Jang Heo (heojang@krei.re.kr), Ki-Whan Chung (kwchung@krei.re.kr)